Wafer‐Scale Growth of Aligned C60 Single Crystals via Solution‐Phase Epitaxy for High‐Performance Transistors. (24th September 2021) - Lu, Zhengjun; Deng, Wei; Fang, Xiaochen; Xiao, Jie; Lu, Bei; Zhang, Xinwei; Pirzado, Azhar Ali Ayaz; Jie, Jiansheng; Zhang, Xiujuan
Abstract: Fullerene (C60 ) single crystals with exceptionally low defects and nearly perfect translational symmetry make them appealing in achieving high‐performance n‐type organic transistors. However, because of its natural 0D structure, control over continuous crystallization of C60 over a large area is extremely challenging. Here, the authors report a solution‐phase epitaxial approach for wafer‐scale growth of continuously aligned C60 single crystals. This method enables the rational control of the density of nucleation event at meniscus front by confining the size and shape of meniscus with a microchannel template. In this case, a single nucleus as seed crystal can be formed at the front of meniscus, and then epitaxial growth from the seed crystal occurs with continuous retreat of the meniscus. As a result, highly uniform C60 single‐crystal array with ultralow defect density is obtained on 2‐inch substrate. Organic field‐effect transistors made from the C60 single‐crystal array show a high average electron mobility of 2.17 cm 2 V −1 s −1, along with a maximum mobility of 5.09 cm 2 V −1 s −1, which is much superior to the C60 polycrystalline film‐based devices. This strategy opens new opportunities for the scalable fabrication of high‐performance integrated devices based on organic crystals. Abstract : Wafer‐scale, continuously aligned C60 single crystals are fabricated via a solution‐phase epitaxial approach, which show high uniformity over a large area (2‐inch) with a low defect density. N‐type organic field‐effect transistors made of the well‐aligned C60 single crystals exhibit high electron mobility, up to 5.09 cm 2 V −1 s −1 .